Detection of Antibodies Against Hog Cholera Virus and Bovine Viral Diarrhea Virus in Porcine Serum: A Comparative Examination Using CF, PLA AND NPLA Assays - Jensen, Merethe Holm (Acta Vet Scand, 1981)
1. A modified direct complement fixation (GF) test, 2. A peroxidase-linked antibody (PLA) assay based on microplates with fixed, viral-antigen containing cells, 3. A neutralization assay carried out in microplates using the “chessboard” principle and read by means of the peroxidaselinked antibody (NPLA) assay. A good correlation was found in their ability to detect the antibodies. Generally neutralizing antibodies could be found 2 weeks after inoculation. By CF and PLA antibodies could be detected at the same time or up to 2 weeks later. All sera were tested by the 3 methods against both HG viral antigen and BVD viral antigen. HC-antibodies could not be distinguished from BVD-antibodies by CF but to a certain degree by PLA. BVD-antibodies could to a certain degree be distinguished from HG-antibodies by CF but not by PLA. This means that CF and PLA together provide a good possibility for differentiation between the two types of antibodies. NPLA could to a high degree of reliability distinguish between HG-antibodies and BVD-antibodies.